2019
DOI: 10.1038/s41374-019-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

False-positive pathology: improving reproducibility with the next generation of pathologists

Abstract: The external validity of the scientific literature has recently come into question, popularly referred to as the "reproducibility crisis." It is now generally acknowledged that too many false positive or non-reproducible results are being published throughout the biomedical and social science literature due to misaligned incentives and poor methodology. Pathology is likely no exception to this problem, and may be especially prone to false positives due to common observational methodologies used in our research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Similarly, access to an adequate case volume is how we ensure pathology's observational research methods are powered to produce accurate results. 10 Patients, mostly unknowingly, have enabled the education and scholarly work of generations of pathologists by allowing their tissue to remain within institutional archives.…”
Section: Privatized Experiencementioning
confidence: 99%
“…Similarly, access to an adequate case volume is how we ensure pathology's observational research methods are powered to produce accurate results. 10 Patients, mostly unknowingly, have enabled the education and scholarly work of generations of pathologists by allowing their tissue to remain within institutional archives.…”
Section: Privatized Experiencementioning
confidence: 99%
“…In these ways, efforts by the cancer research community to characterize mechanisms of metastasis through xenografts, allografts, and genetically engineered animal models are hindered by limited access to pathology expertise, inter-and intra-observer variability, and lack of quantitative and high-throughput methods 22 . Proof-of-principle studies on human tissues have revealed AI-based methods as powerful tools that leverage histological information to classify tumors based on genetic mutations [23][24][25][26] , recurrence, death 27,28 , or response to therapy 29 with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, “ top-down ” approaches involve annotating histopathologic features (histotypes) that have been demonstrated to associate with disease state or outcome (Amin et al, 2017) followed by computation on the multiplexed data to identify underlying molecular patterns. Histopathology has a long history of identifying striking spatial features in small cohorts that do not have prognostic or diagnostic value on follow-up, introducing a note of caution into ‘ bottom-up ’ analysis (Mazer et al, 2019; Voskuil, 2015). At the same time, discoveries arising from ‘t op-down ’ analysis are strongly influenced by prior expectations.…”
Section: Introductionmentioning
confidence: 99%